The Impact of Digitalization on Village Budget Transparency and Accountability - Saputra, Mas Budi; Ermaini, Ermaini; Veronika, Deka (PT. BERBAGI TEKNOLOGI SEMESTA, 2025)
The purpose of this study is to analyze the impact of digitalization on the level of transparency and accountability in budget management in Mekar Sari Village, Muaro District, Jambi Regency. This study uses a quantitative correlational approach with a simple linear regression method. Data were collected through questionnaires administered to village officials and the local community. The analysis results indicate that digitalization has a positive and significant impact on increasing transparency and accountability in village fund management. Advances in digital technology in village administration help improve access to better information and ensure accountability for the use of village funds more effectively. These findings confirm that digitalization is an important tool in improving transparent and accountable village financial management.